Investigation of GAM zonal flows near the pedestal region of H-mode on EAST tokamak - Xi Feng; AhDi Liu; Ge Zhuang; Chu Zhou; X.L. Zou; HaiQing Liu; Lei Ye; ZongLiang Dai; FeiFei Long; S.X. Wang; L. Wang; L.Q. Xu; et al. (Nuclear Fusion)
Geodesic acoustic mode (GAM) is the finite frequency counterpart of zonal flow in toroidal plasmas, which could be excited by and regulate turbulence. This article reports a stationary eigenmode GAM at the inner side of the edge radial electric field contributing to an extreme high confinement plasma with $H_{98}\gt 1.3$ . Such GAM could be observed exclusively in the vicinity of the pedestal top, but not in the pedestal region itself, which represents a previously unreported phenomenon. The bicoherence analysis demonstrates a robust interaction between the GAM and quasi coherent mode (QCM). Statistical evidence indicates that GAMs with such characteristics display a proclivity for a large q _95 and low collisionality in all instances of H-mode accompanied by QCM. Based on the Gyro-kinetic simulation, the QCM is the low n trapped electron mode (TEM) and that the GAM is driven by TEM. Furthermore, the simulations show that the amplitude of GAM declines in conjunction with an increase in the collisionality, which is consistent with the experimental statistics. Additionally, the simulations demonstrate that the turbulent transport exhibits a corresponding decrease as GAM amplitude declines, implying that GAM and its interaction with the QCM would play an important role in the stability and confinement enhancement of such H-mode.